4D printed TPU/PLA/CNT wave structural composite with intelligent thermal-induced shape memory effect and synergistically enhanced mechanical properties. (July 2022) - Huang, Xiayan; Panahi-Sarmad, Mahyar; Dong, Ke; Cui, Ziying; Zhang, Kanglei; Gelis Gonzalez, Orianaisy; Xiao, Xueliang
Graphical abstract: Abstract: Here, a series of polylactic acid/thermoplastic polyurethane (PLA/TPU) blends with multi-walled carbon-nanotubes (MWCNTs) were prepared by extrusion for 3D printing, and the printed samples were in-depth studied for their thermally-induced shape-memory effect and mechanical properties. At first, the morphological analysis revealed that the blends were immiscible, and the MWCNTs have adhered to the TPU phase, thereby improving their interfacial adhesion and enhancing the shape recovery response. Afterwards, the mechanical properties were recorded precisely—some features (tensile strength and Young's modulus) have established descending patterns after incorporating MWCNTs. By contrast, in wave structured (3D-printed) specimens, a systematic rise in tensile strength and Young's modulus was attributed to the wave-length, consistent with the growth of the shape-memory performance (both recovery and fixity). The wave structured PLA/TPU/CNT nanocomposites are capable of ameliorating shape-memory performance and dimensional stability and can put themselves at a premium as a novel shape memory material for a wide range of applications.